When time does not heal all wounds—the use of medical grade honey in wound healing: a case series. (2nd July 2022) - Naik, Piyu Parth; Chrysostomou, Daniela; Cinteza, Mirela; Pokorná, Andrea; Cremers, Niels AJ
Abstract : Objective: Hard-to-heal wounds can be caused by persistent infections or an excess of inflammatory cytokines, proteases and oxidants, and can severely impact the quality of life (QoL) of patients. Due to the paucity of effective treatments and increased resistance to antibiotics, new and improved therapies are required to resolve infections and to simultaneously enhance the healing trajectory. Medical grade honey (MGH) may be a novel and effective treatment approach. Methods: In this case series, we have described six cases of hard-to-heal wounds, and discussed the effects of MGH on infection, wound healing and factors influencing patient QoL (pain, odour and exudate). In all cases, the wounds had persisted for a long period, and previous treatments had been ineffective. Most of the patients had comorbidities, and the majority of the wounds were contaminated with (multiresistant) bacteria, both of which contributed to non-healing. All wounds were treated with L-Mesitran (MGH-based wound care products, Triticum Exploitatie BV, the Netherlands) either as monotherapy or as a complementary therapy. Results: Hard-to-heal wounds started healing, infection was controlled and QoL was strongly improved (malodour, exudate levels and pain swiftly decreased) after the application of the MGH. All wounds healed relatively quickly, considering the severity of the wounds and general health of the patients. Conclusion: In this study, MGH was a useful alternative or complementary therapy to antibiotics and expedited the healing of hard-to-heal wounds.